Trauma, Recovery, and Growth 2008
DOI: 10.1002/9781118269718.ch4
|View full text |Cite
|
Sign up to set email alerts
|

Positive Effects of Terrorism and Posttraumatic Growth: An Individual and Community Perspective

Abstract: We wish to thank Nansook Park and Virginia Navascues chapter and Maitane Arnoso for her invaluable help with for their help in translating this the data search.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 75 publications
3
44
0
Order By: Relevance
“…While heightened anxiety and trauma appear to be a disadvantage for emotional well-being, it is reasonable to think that perhaps individuals who are more anxious about their self and others' well-being will also experience more empathy for others. A phenomenon known as "post-traumatic growth" describes heightened optimistic feelings, prosocial behavior, and trust for the humanity after traumatic events such as terroristic attacks (52)(53)(54).…”
Section: Discussionmentioning
confidence: 99%
“…While heightened anxiety and trauma appear to be a disadvantage for emotional well-being, it is reasonable to think that perhaps individuals who are more anxious about their self and others' well-being will also experience more empathy for others. A phenomenon known as "post-traumatic growth" describes heightened optimistic feelings, prosocial behavior, and trust for the humanity after traumatic events such as terroristic attacks (52)(53)(54).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that a variety of positive emotions can be experienced in the immediate aftermath of stressful events such as a devastating earthquake (Vázquez et al 2005), a massive terrorist attack (Vázquez & Hervas 2010), or in the first 72 hours after a myocardial infarction (Castilla & Vázquez 2011). These findings reveal that even in highly aversive situations, positive appraisal processes may be more common than expected, and also that they may emerge during the events (Vázquez et al 2008).…”
Section: Carmelo Vázquezmentioning
confidence: 96%
“…A few potential mechanisms for this may exist. First, experiences of stressful events have been linked to team members’ development of positive emotions toward one another (e.g., Vázquez, Pérez‐Sales, & Hervás, ). According to the effort justification component of cognitive dissonance theory (Festinger, ), it is plausible that extra effort expended to cope with stressors presented to one's workgroup may result in increased liking of the workgroup to reduce cognitive dissonance.…”
Section: The Ropes Coursementioning
confidence: 99%